The relationship between WhatsApp textisms and the spelling of Spanish adolescents: A case study - Gómez-Camacho, Alejandro; Núñez-Román, Francisco; Conde-Jiménez, Jesús; Perea-Ortega, María de los Ángeles (Círculo de Lingüística Aplicada a la Comunicación, 2025)
The instant messaging application WhatsApp is currently the most widely used means of communication among young Spaniards. This application, along with others of the same type, has favoured the creation of a new written code: digitalk or textese, characterised by the use of textisms, a digital norm that intentionally departs from the academic norm. The aim of this research is to explore the relationship between the textisms of Spanish teenagers on WhatsApp and the normative spelling of their academic texts. It is proposed as a novel study of particular relevance in the Spanish context. The study was carried out with 43 third- and fourth-year student of secondary education in Seville (Spain). Through a descriptive statistical analysis, the characteristics of the digital norm of adolescents on WhatsApp were sought and it was observed that the most common textism is word shortening, followed by others such as the omission of accents and the omission of punctuation marks. On the other hand, it has been observed that the use of textisms in Spanish does not harm the academic spelling of adolescents. Finally, it has been observed that there are some differences in the use of textisms between males and females, with females using a greater number of multimodal elements than males.